Offence-Specific Interventions for Women Convicted of Child Sexual Abuse: Barriers for Program Implementation in Australia - Priebe, Bricklyn (The prison journal, 2025)
There is demand for sexual offending treatment programs (SOTPs) for women sentenced for child sexual abuse in Australia. Yet, formalized programs are currently limited. This research incorporates the views of correctional practitioners via a survey and interviews to establish their perceptions on the feasibility of implementing such programs within Australian custodial settings. Findings indicate that system-level barriers, inadequate tools and expertise, and obstructive attitudes and perceptions present challenges. Evidently, in spite of recent advancements in correctional practice, a range of barriers remain that potentially constrain access to SOTPs for women in custody.